Initial single centre experience with the novel Rhythmia© high density mapping system in an all comer collective of 400 electrophysiological patients. (1st December 2018) - Lackermair, Korbinian; Kellner, Stefanie; Kellnar, Antonia; Riesinger, Lisa M.; Wakili, Reza; Sinner, Moritz F.; Rizas, Konstantinos D.; Fichtner, Stephanie; Estner, Heidi L.
Abstract: Background: A novel, automatically annotating ultra-high density mapping system (Rhythmia©, Boston Scientific) collects a high number and quality of electrograms (EGMs). So far, data on general use in the electrophysiological laboratory are sparse. Methods: We retrospectively analyzed all our ablations using Rhythmia and recorded patient clinical data, procedural parameters, and mapping parameters including the count of EGMs, mapping time, and mapping volume. Where appropriate, procedural parameters were compared over time to assess a learning curve. Results: 400 patients underwent ablation of atrial fibrillation (n = 202), typical (n = 16) or atypical atrial flutter (n = 49), VT (n = 48), PVC (n = 35), accessory pathways (n = 14), AVNRT (n = 4), and focal atrial tachycardia (n = 32). System use was feasible, as no procedure had to be stopped for technical reasons and no ablation had to be withheld because of mapping failure, and safe, with an overall complication rate of 2.25%. Initial restrictions in manoeuvrability of the mapping catheter were overcome rapidly, as indicated by a significant decrease of fluoroscopy time (20 vs. 14 min, p = 0.02), use of contrast agent (50 vs. 40 ml; p < 0.01), and (not significant) lower procedure times (194 vs. 170 min; p = 0.12; comparing the first with the last third of patients undergoing pulmonary vein isolation only procedure). Ablation of complex left atrial, focal and ventricular tachycardias benefited from the reliable automatic annotation of a high number of EGMs. Conclusion: The use of the Rhythmia is feasible and safe. Initial restrictions in manoeuvrability of the Orion mapping catheter were overcome rapidly. The procedures that benefit the most from ultra-high density mapping are complex left atrial tachycardias, focal tachycardias, and ventricular tachycardias. Highlights: By far largest single centre experience of 400 patients treated with a novel ultra-high density 3D mapping system. Documentation of general feasibility and safety. Most benefit in patients with complex arrhythmias with underlying re-entrant mechanisms and focal tachycardias.